Freud, justice and physics (Revista do Tribunal Regional Federal da 3ª Região, 2012)
Throughout Western history, human beings have searched for philosophies that serve as foundations for the rules they have created in order to live in society, in other words, foundations for the very notion of justice. The foundations that have actually been used or merely proposed over this time range from justice based on divine law, through justice based on secular morality to a notion of justice that is totally detached from any moral valuation. The latter is what is currently being sought. A recently released book that has been a hit among legal professionals discusses exactly this: what is the most appropriate philosophical foundation on which to base the edition of rules regulating human life. The name of the book, as released in English, is “Justice: what's the right thing to do?”. In Brazil, it was translated as “Justice: what's the right thing to do?”. Its author is Michael Sandel, an American political philosopher, famous for the course “Justice”, which he taught at Harvard University. This text aims to draw a parallel between this book, the ideas developed by Sigmund Freud in “Civilization and its discontents” and physics, in an attempt to explain, albeit superficially, what philosophy has left out and, therefore, does not have much chance of achieving its intended objective: to substantiate the norms that regulate human relations.
Keywords: justice; moral; physics; Freud